Tax Reform in Chile: Alternative Tax Regimes and Agreements to Avoid Double Taxation - Carey Tagle, Jaime (2014)
On September 29th, 2014, an extensive tax reform was enacted in Chile. The main changes will be applied gradually from October 1, 2014. One of the main changes is the creation of two alternatives income tax regimes that will replace the current integrated regime from year 2017 onwards: (i) the attributed income regime and (ii) the partially integrated regime. The first one will collect the taxes at the foreign-shareholders level on the year the companies generate profits, regardless if they are distributed or not. The second one will raise the overall tax burden for the foreign-shareholders from 35% to 44.45%, unless they are resident of countries that have treaties to avoid the double taxation with Chile.